Comparison of economic cycles morphology based on Polish gross domestic product analysis in years 2000–2013 - Pawęta, Bartosz; Pawęta, Elena (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
For centuries economic fluctuations have been one of the most interesting phenomena to economists of different schools. Despite of different theoretical approaches it is human desire to understand the pattern behind cyclical nature of the economy. In this paper economic cycles in Poland in years 2000–2013 are investigated to verify how cycles morphology changed after the crisis of 2008 and whether they match theoretical characteristics of classic or modern cycle.Results obtained based on analysis of Polish Gross Domestic Product show that the growth rate (although positive) has been lower since the crisis, cycles last for approximately 3.5–4 years, have sharp upper turning points, and turning zones instead of clearly visible troughs. Their length and turning points suggest that in terms of morphology they match characteristics of modern cycle.The importance of this research is high, as it clearly shows that cyclical nature of Polish economy has changed. Findings may be very useful for further research (e.g. similar analysis of other economic aggregates), as well as to those all who are interested in forecasting future economic growth.